Efficacy, effectiveness, and safety of dienogest for the treatment of endometriosis: a systematic review (Revista Contexto & Saúde, 2025)
Endometriosis is a chronic and benign inflammatory disease that affects women of reproductive age and impairs their quality of life. Objective: To investigate the efficacy, effectiveness, and safety of using dienogest in the treatment of endometriosis compared to placebo and medications offered within the Brazilian Unified Health System (SUS). Method: A systematic review was conducted through searches in four scientific databases, following the recommendations of the Cochrane Handbook and reporting according to The PRISMA 2020 statement checklist (PROSPERO: CRD42023388774). Results: Nine studies were included, totaling 1,625 participants. For overall and pelvic pain, the results may favor dienogest over placebo and goserelin. There was no difference between dienogest and triptorelin for overall pain, and dienogest appears to be superior to triptorelin for pelvic pain. Dienogest was non-inferior to leuprorelin. Between dienogest and the other comparators, there was no difference in lower back pain, dyspareunia, pregnancy rate, treatment discontinuation, and total adverse events. Conclusion: Dienogest may be safe when compared to placebo and the drugs available in the SUS. Regarding efficacy and effectiveness, the results suggest the superiority of dienogest compared to placebo and goserelin; non-inferiority compared to leuprorelin, and no difference between dienogest and triptorelin and ethinylestradiol+levonorgestrel; however, the confidence in the evidence is uncertain.
Keywords: Endometriosis; Dienogest; Estradiol; Systematic Review